Failure mechanism of a soil slope and stabilization method: a case study - Kanık, Mustafa (Fırat University, 2022)
In this study, the slope stability problem, which occurred when the projected excavation works of a treatment plant has been started, has been examined. The aim of this study is to determine the conditions causing the slope failure and to make the slope stable again. Then, to ensure the stability of the whole slope after all the excavations work in the project area have been completed. For this purpose, firstly, the topographic features of the slope where the failure took place were determined and a model of the failure condition was created. Field and laboratory studies were used to obtain the data to be used in slope modeling. Models reflecting the current situation were analyzed considering static and dynamic conditions and a safe slope design was created. The analyzes are carried out by Slide V.6.0. software which is based on limit equilibrium methods and Bishop Method was preferred. As a result, it was determined that the reason of the failure occurred was the change of the soil’s physical and mechanical parameters due to precipitation. In the slope stability problem considered, the benching method has been proposed as an improvement method, and additionally, suggestions have been made for the disposal of surface waters by drainage methods.
Keywords: General Geology; Genel Jeoloji